AN ARCHITECTURAL APPROACH COMBINING 3D SCANNING AND UNPUBLISHED ARCHIVES TO THE ANALYSIS OF A 19TH-CENTURY ENGINEERING STRUCTURE: CASE STUDY OF THE CHIFFA RAILWAY VIADUCT ALGERIA - Dahbia Haddad; Bousaad Aiche; Mebarek Khelfi (International Journal of Innovative Technologies in Social Science, 2025)
The engineering structure we are about to analyse is the result of several successive phases. The reasons for its current form will find their justification in the history of this structure, which is undeniably linked to a railway renewal that Algeria experienced during the colonial period. The focus is on the twentieth-century restoration (renovation) of the railway bridge that spans the Chiffa River. This bridge was originally built in the nineteenth century as part of the Algiers-Oran railway line. The purpose of this exploratory paper is to trace the history of this structure since its construction and to document an experiment conducted in 1930 involving the revewal of metal railway structures on the mentioned line. One aspect of the study focuses on the design of old metal structures, while another looks into the technical aspects of reinforcing these structures with reinforced concrete. This reinforcement was required because of the use of reinforced concrete during the railway renewal, which modernized techniques. Furthermore, it addresses the latter’s doubling specifically in terms of its scientific and technological contributions at the time. The experiment was carried out using field surveys, 3D scanning, and analysis of archived materials from the National Society of Rail Transport archives (SNTF).